DIMENSION OF KYIVAN RUS PAGAN ICONOGRAPHY - Богомолець, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article reveals the peculiarities of transformation of Byzantine iconography and temple construction on the territory of Kievan Rus. The general nature of guarding temple construction of and revealed the dominance of the cult of the Virgin reflected on this background. There was shown marginalization image and icon of Christ in the Slavic world view, which is displayed in the article, was due to the influence of traditional for agriculture culture archetype Mother. Along with the others the polysemantic content of the image “Virgin Oranta” was found, and stressed its Slavic origins.